Determination of hydraulic conductivity of fractured rock masses : a case study for a rock cavern project in Singapore - Zhao, Zhiye (2015)
In order to reduce the risk associated with water seepage in an underground rock cavern project in Singapore, a reliable hydro-geological model should be established based on the in situ investigation data. The key challenging issue in the hydro-geological model building is how to integrate limited geological and hydro-geological data to determine the hydraulic conductivity of the fractured rock masses. Based on the data obtained from different stages (feasibility investigation stage, construction stage, and post-construction stage), suitable models and methods are proposed to determine the hydraulic conductivities at different locations and depths, which will be used at other locations in the future.